Hubungan Pengetahuan dan Sikap Pasien dengan Kepatuhan Penatalaksanaan Diabetes Melitus di Poliklinik Khusus Penyakit Dalam RSUP Dr. M. Djamil Padang - Mohd Jamil; Dorisnita Dorisnita; Linda Ardayanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Diabetes Mellitus management compliance in the important aspect in controlling blood sugar levels. Compliance is inseparable from the knowledge and attitudes of individuals because these factors are the main drivers in shaping a behavior. This study aims to determine the relationship between knowledge and attitudes of patients with adherence to diabetes mellitus management in a specific polyclinic in RSUP DR. M. Djamil Padang. This research was conducted in a special clinic for internal medicine Dr. M. Djamil Padang. This research is a quantitative research with crosssectional -conducted on 49 respondents using the purposive Sampling. The results of statistical tests using the chi-square obtained p value, namely 0.031 and 0.000, which means that there is a significant relationship between knowledge and attitudes of patients with adherence to diabetes mellitus management. It is hoped that health services can improve patient compliance in diabetes mellitus management through optimal health education programs.